Profile Changes in Weight and Body Mass Index of Single Rod Levonorgestrel Implant Acceptor (MonoplantÂ®): Profil Perubahan Berat Badan dan Indeks Masssa Tubuh Akseptor Implan Levonorgestrel Satu Batang (MonoplantÂ®) - Eka R. Gunardi; Jimmy T. Sitorus (Indonesian Journal of Obstetrics and Gynecology, 2020)
AbstractObjective: To finding out the change of weight and body mass index (BMI) of single rodlevonorgestrel implant acceptor (Monoplant®).Methods: A cross-sectional descriptive study was conductedusing data changes of weight and BMI obtained from series of measurement which is recorded in patients’ medical record in three years of Monoplant® placement in Raden Saleh Clinic, Jakarta. This method is the part of a research of a bigger phase two in clinical test.Results: From 21 subjects of this research, the average weight and BMI before and after 3 years of Monoplant® placement is gained, i.e. 53.1 (SD 11,0) kg and 22.4 (SD 4.5) kg/m2, and 54.8 (SD 9.4) kg and 23.1 (SD 3.9) kg/m2. Despite the tendency of increasing, statistically the increasing of weight and BMI, however, is meaningless (p=0.09) and (p=0.08). There is a difference of weight in series of measurement, particularly after the 12th month (Repeated test ANOVA p=0.024). Even though there is no difference in BMI average, there is a difference in subject's proportion based on BMI categories before and after Monoplant® placement (Marginal homogeneity test p=0.046). The increasing of levonorgestrel level occurs in the 6th month and subsequently followed by the increase of BMI in the 12th month.Conclusions: There is a tendency of increasing weight and BMI in Monoplant® users, specifically after one year despite statistically insignificant.Keywords: levonorgestrel, monoplant®, weight, body mass index. AbstrakTujuan: Untuk mengetahui perubahan berat badan dan indeks massa tubuh pada akseptor implan levonorgestrel satu batang (Monoplant®).Metode: Studi deskriptif dengan desain potong lintang mengambil data perubahan BB dan IMT diperoleh dari pengukuran serial yang tercatat dalam rekam medis pasien selama tiga tahun pemasangan Monoplant® di Klinik Raden Saleh, Jakarta. Penelitian ini merupakan bagian dari suatu penelitian uji klinis fase 2 yang lebih besar.Hasil: Dari 21 subjek penelitian ini, didapatkan rerata BB dan IMT sebelum dan setelah 3 tahun pemasangan Monoplant®yakni 53,1 (SB 11,0) kg dan 22,4 (SB 4,5) kg/m2, serta 54,8 (SB 9,4) kg dan 23,1 (SB 3,9) kg/m2. Meskipun ada kecenderungan naik, tetapi secara statistik kenaikan BB dan IMT tersebut tidak bermakna (p=0,09) dan (p=0,08). Terdapat perbedaan berat badan dalam pengukuran serial, terutama setelah bulan ke-12 (Uji repeated ANOVA p=0,024). Walaupun tidak terdapat perbedaan rerata IMT, terdapat perbedaan proporsi subjek berdasarkan kategori IMT sebelum dan setelah pemasangan Monoplant® (Uji Marginal homogeinity p=0,046). Peningkatan kadar levonorgestrel terjadi pada bulan ke-6 yang kemudian diikuti oleh kenaikan IMT pada bulan ke-12.Kesimpulan: Terdapat kecenderungan peningkatan BB dan IMT pengguna Monoplant®, khususnya setelah satu tahunmeskipun secara statistik tidak bermakna.Kata kunci: berat badan, indeks massa tubuh, levonorgestrel, monoplant®.